Schlumberger Procurement and Support Services Sdn Bhd / Nur Shariena Md Heshamuddin - Md Heshamuddin, Nur Shariena (Faculty of Business and Management, 2023)
In this Internship Report, there are nine parts of the contents. The first part of the report is the Preliminary Pages which consist of Executive Summary, the second part which is the resume Table of Content and of the report is the and some information Acknowledgment. Students ' Profile. The third part of the report is more into knowing the company background which the content consists of Location, Background, Vision and Mission, Objective, Goal, The Organizational Structure and Products and Services that being provided by the company. The forth part of the report will be discussed about the Training Reflection, in training reflection where is the task scope during date of the responsibility and Extrinsic start and that being gives and job follows with the specific end, department, roles, given. It also discusses on the Intrinsic benefits that the company provide to the interns. the internship time, its internship that being benefit the fifth part is the SWOT analysis which the identification of two observation foreach SWOT elements. Part six is discussion and recommendation part which each of SWOT need to be explain further and provide the recommendation for the companies on how to improve the implementation in the company. Part seven is the part where the conclusion on the report which summaries of the important part in the report. The eight part is the references of the report with the APA style and lastly, the appendices on the picture of the article related and website of the company.